1992
DOI: 10.1159/000175013
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Valve Area Underestimation by the Continuity Equation

Abstract: During the last years, noninvasive determination of the aortic valve area by Doppler echocardiography using the continuity equation became popular. However, a systematic valve area underestimation of about 15 % compared to invasive measurements using the Gorlin formula has been reported. The cause therefore is unknown. The purpose of this study was to evaluate whether the valve area underestimation by the Doppler method might be due to differences in the hydrodynamic background of both methods. This comparison… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
5
0

Year Published

1996
1996
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 12 publications
1
5
0
Order By: Relevance
“…A trend towards underestimation of AVA was seen, when diameter derived estimations of ALVOT were used compared to direct AVA planimetry (0.89 ± 0.38 cm 2 vs. 1.00 ± 0.4 cm 2 ). It has long been observed that echo derived estimates of AVA are often smaller than those estimated using invasive techniques [10][11][12][13]. Our findings that ALVOT is frequently underestimated when diameter-derived calculation is used, may account for some of the observed discrepancy between echo and invasively determined AVA measurement.…”
Section: Discussionmentioning
confidence: 62%
“…A trend towards underestimation of AVA was seen, when diameter derived estimations of ALVOT were used compared to direct AVA planimetry (0.89 ± 0.38 cm 2 vs. 1.00 ± 0.4 cm 2 ). It has long been observed that echo derived estimates of AVA are often smaller than those estimated using invasive techniques [10][11][12][13]. Our findings that ALVOT is frequently underestimated when diameter-derived calculation is used, may account for some of the observed discrepancy between echo and invasively determined AVA measurement.…”
Section: Discussionmentioning
confidence: 62%
“…Using 2D echocardiography (2DE), the aortic valve area (AVA) is usually calculated with the continuity equation. The continuity equation (CE) has shown concordance with invasive techniques but with consistent underestimation 1–3 . The commonly used formulation of the continuity equation relies on assumptions about both the geometry of the left ventricular outflow tract (LVOT) and the applied imaging planes.…”
mentioning
confidence: 99%
“…Two‐Dimensional Echocardiography Two‐dimensional measurement of the left ventricular outflow tract diameter (DLVOT‐2D) was performed immediately underneath the aortic valve from trailing to leading edge during peak systole when the aortic cusps were maximally separated. Images were viewed on a digital review station (Medcon, Tel Aviv, Israel) and the approximated cross‐sectional area of the left ventricular outflow tract (ALVOT‐2D) was calculated using π× radius 2 . The images were analyzed by two readers (DM and BK) who were blinded to each other's findings.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This method would also allow modifying the continuity formula regularly used in the estimation of the aortic valve area (AVA). It is usually considered that AVA measurement using continuity equation over-estimates the severity of the aortic stenosis [9][10][11]. This could be partly because the area is estimated and not directly measured, underestimating the numerator factor of the equation.…”
Section: Discussionmentioning
confidence: 99%